Relationship Between Stress Levels With the Ankle Brachial Index (ABI) Value as Early Detection of Peripheral Arterial Disease (PAD) and Diabetes Mellitus Type II - Agus Priyanto; Abdillah, Alvin; Mukallalah, Raudhotul (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
As they age, many seniors experience stress. Stress is a person's inability to cope with challenges, which can lead to increased blood sugar. Blood sugar is a source of energy for energy production. One indicator for detecting PAD is the ABI. is a diagnostic examination of the lower extremities to detect the possibility of decreased peripheral perfusion by comparing the systolic pressure of the ankle and arm. Research This aim to analyze the relationship between stress levels and blood sugar with the Ankle Brachial Index (ABI) value as an early detection of Peripheral Arterial Disease (PAD) in type II diabetes mellitus patients at the Elderly Posyandu, Mlajah Village, Bangkalan. This type of research is analytic correlation with cross-sectional design The population in this study was the entire population of type II DM patients at the Elderly Posyandu, Mlajah Village, Bangkalan with a total of a sample of 42 respondents, using the probability sampling technique , namely simple random sampling . Variables Independent Stress Level and Variables dependent ABI value with research statistical test use Spearman rank obtained the p value (0.000) with a significance level of α (0.05), meaning the p value <α with the conclusion that there is connection between level stress and sugar blood with ABI value . Based on the interpretation table of stress levels with ABI values, the r value is (0.516), and the interpretation table of blood sugar with ABI values, the r value is (0.636) so that the correlation between the two variables can be said to be strong. Stress levels, blood sugar levels, and ABI values are related. This research is expected to help the public, especially those with diabetes mellitus who participated, improve their health.